Decrease in primary but not in secondary abdominal surgery for Crohn's disease: nationwide cohort study, 1990–2014. Issue 11 (26th May 2020) - Kalman, T. D.; Everhov, Å. H.; Nordenvall, C.; Sachs, M. C.; Halfvarson, J.; Ekbom, A.; Ludvigsson, J. F.; Myrelid, P.; Olén, O.
Abstract : Background: Treatment of patients with Crohn's disease has evolved in recent decades, with increasing use of immunomodulatory medication since 1990 and biologicals since 1998. In parallel, there has been increased use of active disease monitoring. To what extent these changes have influenced the incidence of primary and repeat surgical resection remains debated. Methods: In this nationwide cohort study, incident patients of all ages with Crohn's disease, identified in Swedish National Patient Registry between 1990 and 2014, were divided into five calendar periods of diagnosis: 1990–1995 and 1996–2000 with use of inpatient registries, 2001, and 2002–2008 and 2009–2014 with use of inpatient and outpatient registries. The cumulative incidence of first and repeat abdominal surgery (except closure of stomas), by category of surgical procedure, was estimated using the Kaplan–Meier method. Results: Among 21 273 patients with Crohn's disease, the cumulative incidence of first abdominal surgery within 5 years of Crohn's disease diagnosis decreased continuously from 54·8 per cent in 1990–1995 to 40·4 per cent in 1996–2000 ( P  < 0·001), and again from 19·8 per cent in 2002–2008 to 17·3 per cent in 2009–2014 ( P  < 0·001). Repeat 5‐year surgery rates decreased from 18·9 per cent in 1990–1995 to 16·0 per cent in 1996–2000 ( P  = 0·009). After 2000, no further significant decreases were observed. Conclusion: The 5‐year rate of surgical intervention for Crohn's disease has decreased significantly, but the rate of repeat surgery has remained stable despite the introduction of biological therapy. Abstract : In a Swedish population‐based database, the cumulative incidence of a first abdominal surgical procedure after a diagnosis of Crohn's disease has decreased by two‐thirds over the past 25 years. The risk of repeat abdominal surgery has not decreased since the introduction of biologicals. Ileocaecal resection remained the most common procedure during the study interval, but the 5‐ and 10‐year risk of repeat ileocolic resection was only 4·4 and 8·8 per cent respectively. Decreasing surgery Abstract : Antecedentes: El tratamie nto de pacientes con enfermedad de Crohn ha evolucionado en las últimas décadas con un uso cada vez mayor de medicamentos inmunomoduladores desde 1990 y tratamientos biológicos desde 1998. Al mismo tiempo, ha aumentado la utilidad de la vigilancia activa de la enfermedad. Hasta qué punto estos cambios han influido en la incidencia de la resección quirúrgica primaria y repetida sigue siendo objeto de debate. Métodos: Estudio de cohortes a nivel nacional de pacientes incidentes con enfermedad de Crohn de todas las edades identificados en el registro sueco nacional de pacientes entre 1990‐2014, que se dividió en cinco períodos de diagnóstico: 1990‐1995 y 1996‐2000 con el uso de registros de pacientes hospitalizados, 2001, y 2002‐2008 y 2009‐2014 con uso de registros de pacientes ambulatorios y hospitalizados. Se estimó la incidencia acumulada de la primera cirugía abdominal y de las cirugías abdominales subsiguientes (excepto el cierre de estomas), por categoría de procedimiento quirúrgico, mediante el método de Kaplan‐Meier. Resultados: Entre 21.273 pacientes con enfermedad de Crohn, la incidencia acumulada de la primera cirugía abdominal durante los 5 años posteriores al diagnóstico de la enfermedad disminuyó continuamente del 54, 8% en la cohorte 1990‐1995 al 40, 4% en la cohorte 1996‐2000 ( P < 0, 001) y nuevamente del 19, 8% en cohorte 2002‐2008 al 17, 3% en la cohorte 2009‐2014 ( P < 0, 001). Las tasas cirugías iterativas a los 5 años disminuyeron de 18, 9% en la cohorte 1990‐1995 a 16, 0% en la cohorte 1996‐2000 ( P = 0, 017). Después del 2000, no se observaron más disminuciones significativas. Conclusión: La tasa de intervención quirúrgica a los 5 años para la enfermedad de Crohn ha disminuido significativamente, pero la cirugía iterativa se ha mantenido estable a pesar de la introducción de la terapia biológica.